Empirical Investigation of an Equity Pairs Trading Strategy - Chen, Huafeng (Jason); Chen, Shaojun (Jenny); Chen, Zhuo; Li, Feng (Management Science, 2019)
We show that an equity pairs trading strategy generates large and significant abnormal returns. We find that two components of the trading signal (i.e., short-term reversal and pairs momentum) have different dynamic and cross-sectional properties. The pairs momentum is largely explained by the one-month version of the industry momentum. Therefore, the pairs trading profits are largely explained by the short-term reversal and a version of the industry momentum. The online appendix is available at https://doi.org/10.1287/mnsc.2017.2825 . This paper was accepted by Lauren Cohen, finance.